Penggunaan Media Picture And Picture Untuk Meningkatkan Kreativitas Belajar Pada Materi Part Of Body Di Sekolah Nida Suksasat School Satun Thailand - Sipahutar, Rafika Sari; Basri, Amin; Perwita Sari, Suci (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to determine the analysis of the use of picture and picture media to increase learning creativity in part of the body material at Nida Suksasat School Satun Thailand. This research methodology is qualitative research which describes data using a series of sentences (Moleong, 2018). To collect, observation, interviews and documentation approaches were used as research data collection techniques. The researcher's data analysis process includes data reduction, data presentation, and drawing conclusions. The results of this research indicate that the analysis of the use of picture and picture media at the Nida Suksasat School, Satun Thailand, uses learning media to increase learning creativity in Part of the Body material for fourth grade students at the Nida Suksasat School, Satun Thailand, that the Picture and Picture learning media greatly influences students' interest in learning. Study. This is in accordance with Arsyad's (2010) statement that the use of Picture and Picture learning media in the teaching and learning process can arouse students' interest or desire to learn. At the first meeting the teacher only used LKS books and it was seen that the students' creativity in learning was slightly lacking and the students looked more passive. In contrast to the second meeting where the teacher used more interesting media, namely using Picture and Picture, it could be seen that students' creativity in learning was increasing and students looked more active. Student activity can be seen when the teacher actively asks questions to students, students answer immediately and when they feel they do not understand what the teacher is saying, students will immediately ask the teacher without feeling embarrassed. Students also feel happy and enjoy every process in learning. With the existence of learning media, the learning process will take place effectively and this will have a positive impact on learning outcomes. Good learning outcomes can be realized because there is a good and optimal learning process. A good learning process can be created because there is learning media that supports it.